Ultrasonication effects on physicochemical and emulsifying properties of Cyperus esculentus seed (tiger nut) proteins. (May 2021) - Cui, Qiang; Wang, Lin; Wang, Guorong; Zhang, Anqi; Wang, Xibo; Jiang, Lianzhou
Abstract: In this study, the effects of ultrasonication (0, 200, 300, 400, 500 and 600 W) on the intrinsic fluorescence spectra, surface hydrophobicity (H0 ), particle size, ultraviolet (UV) spectra, emulsifying properties and solubility properties of Cyperus esculentus seed protein (CEP) solutions were investigated. An increase in ultrasound power significantly improved emulsifying activity and emulsion stability of CEP (P < 0.05). After ultrasonication, the solubility of CEP increased from 41.29% to 67.53%. Various spectral methods, such as the Fourier infrared spectroscopy, fluorescence spectroscopy, and ultraviolet spectroscopy, showed that ultrasonication changes the structure of the CEP protein, expose the water-transporting groups, and improves the hydrophobicity of the surface. The particle size and turbidity of the protein emulsion significantly decreased after ultrasound treatment, indicating that the particles in the protein solution became smaller and more uniformly distributed. The scanning electron microscopy (SEM) confirmed the results, verifying that the protein particle size was dramatically reduced after ultrasound treatment. This study provides a theoretical basis for the application of CEP in food processing. Highlights: Cyperus esculentus (CEP) is a new source of functional proteins. For the first time, the structural properties of CEP were studied. Ultrasonic treatment of CEP significantly improved functional properties. Promote CEP applications and development in the food industry.